(untitled) (REMUNOM, 2026)
This research had the general objective of analyzing the view of teachers at IFMA/Campus São João dos Patos on the use of the History of Mathematics in their teaching practices. This work sought to discuss the importance of the History of Mathematics as a pedagogical trend as well as investigate how the Textbook deals with this subject. As a methodological path, bibliographical research, case study and qualitative-quantitative approach were used. For data collection, Google Forms was used to seek teachers’ opinions on the topic, and graphs and tables were used for data analysis. After carrying out this work, it was found that teachers recognize the relevance of the History of Mathematics in teaching, and discussed the importance of this approach. However, most teachers did not use it in their teaching practice. It was also found that the Textbook used needs improvement in its approach in relation to historical contextualization.